Women of Steel : articulations of empowerment and livelihood practices in the Dwars River Valley, Western Cape - Van der Heijden, Ingrid (Stellenbosch : Stellenbosch University, 2009)
Thesis (MA (Sociology and Social Anthropology))--Stellenbosch University, 2009.